The CMA steps up enforcement of procedural merger control rules: key lessons from recent cases. Issue 1 (April 2020) - Jephcott, Mark; Allen, Ruth
Abstract : The powers of the CMA to obtain information about a merger and to prevent (or even unwind) integration of merging businesses pending the conclusion of an investigation into the competitive effects of the merger are an extremely important part of the UK's voluntary merger control regime, which has no mandatory notification or standstill obligations. The CMA has adopted a series of decisions over the last two years which indicate that it is taking an increasingly robust approach to compliance with notices and orders issued in this context. This is line with both the global trend towards tougher enforcement of procedural merger control rules, and the CMA's increasingly strict approach to enforcement of procedural rules in other contexts, such as antitrust investigations and market studies. This article explores this trend and highlights some key lessons from recent cases for merging parties and their advisers, focussing in particular on fines imposed for breach of interim measures and non-compliance with formal information requests. It also identifies some possible reasons for the toughening of the CMA's stance including, in particular, the interplay with the anticipated impact of Brexit.